Steady and Unsteady Casingwall Flow Phenomena in a Single-Stage Low-Speed Compressor at Part-Load Conditions - H. Saathoff; A. Deppe; U. Stark; M. Rohdenburg; H. Rohkamm; D. Wulff; G. Kosyna (International Journal of Rotating Machinery)
This article describes an investigation of the casingwall flow phenomena in a single-stage, axial-flow, low-speed compressor at part-load conditions, utilizing an oil-flow technique to visualize the boundary layer development and highfrequency sensors to measure ensemble-averaged velocity and flow-angle distributions as well as unsteady total pressure distributions. Representative results are shown and discussed. The results enable different sources of endwall blockage to be identified and changes with flow rate to be determined.